Bridging the Economic Divide within Nations : A Scorecard on the Performance of Regional Development Policies in Reducing Regional Income Disparities - Shankar, Raja; Shah, Anwar (World Bank, Washington, DC, 2014)
Regional inequalities represent a continuing development challenge in most countries, especially those with large geographic areas. Globalization heightens these challenges because it places a premium on skills: since rich regions typically also have better educated and better skilled labor, the gulf between rich and poor regions widens. While central governments in unitary states are relatively unconstrained in their choice of policies for reducing regional disparities, in a federation the division of powers curtails federal flexibility in policy choice. Thus in federal states large regional disparities can represent serious threats, with the state's inability to deal with such inequities creating potential for disunity and, in extreme cases, for disintegration. Inequalities beyond a threshold may lead to calls for separation by both the richest and the poorest regions. While the poorest regional may consider the inequalities a manifestation of regional injustice, the richest regions may view the union with the poorest regions as holding them back in their drive toward prosperity. Under these circumstances, there is a presumption in development economics that decentralized fiscal arrangements would lead to ever widening regional inequalities. The authors provide an empirical test of this hypothesis. The authors conclude that regional development policies have failed in almost all countries, federal and unitary alike. Among 10 countries with high or substantial regional income inequality, only one (Thailand) has experienced convergence in regional incomes. Still, federal countries do better in restraining regional inequalities, because of the greater political risk these disparities pose for such countries. The authors classify countries by degree of convergence in regional incomes: a) Countries experiencing regional income divergence - Brazil, China, India, Indonesia, the Philippines, Romania, the Russian Federation, Sri Lanka, and Vietnam. b) Countries experiencing no significant change in regional income variation - Canada and Mexico. c) Countries experiencing regional income convergence - Chile, Pakistan, Thailand, the United States, and Uzbekistan. Regional development outcomes observed in these countries provide a revealing look at the impact of regional development policies. While countries experiencing divergence tend to focus on interventionist policies, those experiencing convergence have taken a hands-off approach to regional development and instead focused on promoting an economic union by removing barriers to factor mobility and ensuring minimum standards in basic services across the nation. In Chile, for example, convergence in regional incomes is largely attributable to liberalizing the economy and removing distortions so that regions could discover their own comparative advantage. In Pakistan and the United States convergence is attributable to greater factor mobility. Paradoxically, creating a level playing field helps disadvantaged regions more than do paternalistic protectionist policies.